Pengaruh Social Media Marketing dan Brand Credibility Terhadap Purchase Intention Dengan Customer Attitude Sebagai Variabel Interverning Pada Pengguna Aplikasi Gojek (Studi Kasus Pada Mahasiswa Universitas Islam Malang Angkatan 2020) - Putra, Arif Rahman Surya; Mardani, Ronny Malavia; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze and describe the influence of Social Marketing and Brand Credibility on Purchase Intention with Customer Attitude as an Intervening Variable among Gojek Application Users (Study on Students of the Islamic University of Malang Class of 2020). The population in this study is undergraduate students of the Islamic University of Malang Class of 2020 from 10 faculties with a total of 2,347 students. Then from that number a sample of 85 people was taken using the maholtra formula. The variables used in this study are the dependent variable Purchase Intention, the independent variables Social Media Marketing and Brand Credibility, and the intervening variable Customer Attitude. The data analysis technique in this study uses path analysis with the help of SPSS 25 software. The results show that 1) Social Media Marketing directly has a significant effect on Customer Attitude 2) Brand Credibility directly has a significant effect on Customer Attitude 3) Social Media Marketing directly has a significant effect on Purchase Intention 4) Brand Credibility directly has a significant effect on Purchase Intention 5) Customer Attitude directly has a significant effect on Purchase Intention 6) Social Media Marketing indirectly has a significant effect on Purchase Intention through Customer Attitude 7) Brand Credibility indirectly has a significant effect on Purchase Intention through Customer Attitude. Keywords: Social Media Marketing, Brand Credibility, Purchase Intention, Customer Attitude